Pulmonary Embolization of Radiolucent Intravenous Cannula: Endovascular Retrieval - Giragani, Suresh; Singh, Manish Kumar; Gonuguntla, Hari kishan; Muthyala, Swathi; Alwala, Surender (Indian Journal of Radiology and Imaging, 2021)
Fracture and embolization of peripheral intravenous cannula is very rare. Although endovascular retrieval is the standard of care for most of the embolized intravascular devices, endovascular management of embolized peripheral intravenous cannula is technically difficult due to its radiolucent nature and it is not described previously in the literature. We describe the clinical presentation, imaging findings, and endovascular management in a middle aged male who had fractured peripheral intravenous cannula which was embolized into the pulmonary artery branch. Technical nuances associated with retrieval of this radiolucent little plastic tube have been discussed.
Keywords: intravenous cannula; pulmonary artery; endovascular retrieval